Duration and onset of effect of incobotulinumtoxinA for the treatment of blepharospasm in botulinum toxin-naïve subjects. (3rd October 2021) - Mitsikostas, Dimos D.; Dekundy, Andrzej; Hanschmann, Angelika; Althaus, Michael; Scheschonka, Astrid; Pagan, Fernando; Jankovic, Joseph
Abstract: Objective: Blepharospasm is a focal dystonia whereby excessive eyelid muscle contractions cause involuntary eye closure. Botulinum neurotoxin type A (BoNT-A) injections are an approved treatment. This randomized placebo-controlled trial (NCT01896895; EudraCT number 2012-004821-26) assessed the efficacy, safety, and treatment effect duration of incobotulinumtoxinA (Xeomin, Merz Pharmaceuticals GmbH), a BoNT-A formulation without complexing proteins, in BoNT-A-naïve adults with blepharospasm. Methods: Subjects received incobotulinumtoxinA 50 U, 25 U (total dose) or placebo during a main study period (MP; 6–20 weeks). Patients needing a second injection received incobotulinumtoxinA ≤70 U in an open-label extension period (EP; 6–20 weeks). Treatment effect durations were time from first injection to EP injection or final MP visit and from EP injection to end-of-study visit. Times to effect onset and to waning of effect (MP) were time from injection to first subject-assessed onset effect and time from injection to subject-reported waning of effect, respectively. Results: Of 61 subjects, 39 entered the EP. During the MP, median duration of treatment effect was longer with incobotulinumtoxinA 50 U (20 weeks) versus incobotulinumtoxinA 25 U (11 weeks) or placebo (6 weeks). Median duration of treatment effect was 20 weeks during the EP. Median time to effect onset was 5, 7, and 14 days with 50 U, 25 U, and placebo, respectively ( p = .022 for 50 U versus placebo). Median time to waning of treatment effect was comparable between groups. Conclusion: Subjects reported an effect onset from 5 days after injection lasting up to 20 weeks (maximum observation period). Data indicate that incobotulinumtoxinA re-treatment of blepharospasm may not be required at fixed 12-week intervals and provide evidence for a patient-tailored approach. PLAIN LANGUAGE SUMMARY: Blepharospasm is a condition in which involuntary contractions of the eyelid muscles cause the eye to close. The condition can be treated with botulinum neurotoxin type A (BoNT-A) injections. This study assessed the duration of effect and time to onset of effect for the BoNT-A formulation incobotulinumtoxinA (Xeomin, Merz Pharmaceuticals GmbH) in adults with blepharospasm. Subjects received a single injection of one of two doses of incobotulinumtoxinA (total dose 25 or 50 U) or placebo and received a second injection of incobotulinumtoxinA only (total dose ≤70 U; the second injection was not compared with placebo) if needed 6–20 weeks after the first injection. After the first injection, the median (mid-point of values from all subjects) duration of treatment effect was longer with the higher incobotulinumtoxinA dose (20 weeks) than with the lower dose (11 weeks) and was longer with both incobotulinumtoxinA doses than with placebo (6 weeks). After the second incobotulinumtoxinA injection, the median duration of treatment effect was 20 weeks. The time to onset of effect was quicker with both incobotulinumtoxinA doses (5 and 7 days for the higher and lower doses, respectively) than with placebo (14 days) and the difference was statistically significant for the higher incobotulinumtoxinA dose compared with placebo. The time to waning of treatment effect was similar for the two incobotulinumtoxinA doses and placebo. This study shows that incobotulinumtoxinA is an effective treatment for blepharospasm, with a fast onset of action. In addition, the effects of one injection can last for up to 20 weeks.